Travails of Mentally Challenged Relatives Coping with Care in Thulamela Municipality - Matambela, Konanani Constance; Tshifhumulo, Rendani (International Journal of Criminology and Sociology, 2021)
Background: Forensic psychiatric hospital usually deal with the problem of rejection of mentally ill patient by their families. Families report finding the burden of caring for their mentally Ill relatives who are also capable of committing crimes such as rape, murder and arson unbearable. They have to account for their crimes in the communities and often experience stigma. The family feels judged by both the society and health care professionals when they are unable to cope with the caregiving role. A lot of research on mental illness emphasises more on experiences of mental health care users and the caregiver of these mentally ill family members. Aim: The study seeks to narrate the toils of mentally ill relatives caring for the sick. Setting: The study was conducted in 2018 with caregivers of mentally ill patients in Thulamela municipality within the Vhembe district in Limpopo province. Method: The study was qualitative in nature and an explorative and descriptive study design was used. Five families with relatives being rehabilitated at Hayani psychiatric hospital were chosen using convenience sampling. A focus group was used to collect data from the five families. Data was analysed thematically following the six stages of thematic data analysis. Results: The study found that caregivers experience emotional, physical, financial, and social strains from caring for their mentally ill relative. They attempt to cope by seeking spiritual guidance and family support. Conclusion: The forensic mental health system should device special programs that focus on coordinating, capacitating health practitioners and monitoring family care givers support services. Future study that focuses on assessing why health care practitioners are not willing to offer support services to our family care givers should be conducted.